Letter (copy) : Situation in Spain - Citrine, Walter, 1887-1983
011-0054-001 WMC/KMS/732 Secretary's. 26th August, 1937 Mr. W. Schevenels, 15, Sq. de Chatillon, PARIS. XIV. Dear Schevenels, I attach a copy of a letter which I have sent to you at the I.F.T.U. offices, suggesting you should cone over here on Monday or Tuesday next, 30th or 31st August, to talk over the situation in Spain. Needless to say if you can come I should be very glad if you can stay with us at Wembley. I am sure that Koun would be glad to see you, although I have not told him I an writing to you. I am rather anxious to know as much as possible about the situation in Spain, and particularly about the intrigues which are going on there. Let me know as soon as you can whether you can manage it. Your sincerely, Enc. Copy of letter. 292/946/11/54